2013
DOI: 10.2478/v10304-012-0041-5
|View full text |Cite
|
Sign up to set email alerts
|

Pure chitosan microfibres for biomedical applications

Abstract: Due to its excellent biocompatibility, Chitosan is a very promising material for degradable products in biomedical applications. The development of pure chitosan microfibre yarn with defined size and directional alignment has always remained a critical research objective. Only fibres of consistent quality can be manufactured into textile structures, such as nonwovens and knitted or woven fabrics. In an adapted, industrial scale wet spinning process, chitosan fibres can now be manufactured at the Institute of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…In addition, the viscosity shows a strong dependence on the concentration of the spinning solutions, which increases significantly with higher solids content. Shear rates of about 1 s −1 represent the range close to the spinning process on an industrial spinning plant [ 42 ]. At this point spinning dopes of CHS-02 show relatively low viscosities, primarily due to the low molecular mass.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the viscosity shows a strong dependence on the concentration of the spinning solutions, which increases significantly with higher solids content. Shear rates of about 1 s −1 represent the range close to the spinning process on an industrial spinning plant [ 42 ]. At this point spinning dopes of CHS-02 show relatively low viscosities, primarily due to the low molecular mass.…”
Section: Resultsmentioning
confidence: 99%
“…The solubility of chitosan is based on a protonation of the amino groups. The extruded chitosan threads are precipitated into continuous filaments within an alkaline coagulation bath (e.g., by sodium hydroxide) for wet spinning [165][166][167] and within an alkaline ammonia gas phase for dry spinning [168] by deprotonating the amino groups of the chitosan. To improve the mechanical characteristics of chitosan yarns, spinning solutions can be prepared using ionic liquids [169] and incorporating additives such as chitin [170] and nanocellulose particles [171].…”
Section: Chitosan Filament Yarnsmentioning
confidence: 99%
“…Plasma treatment was applied to improve adhesion by increased cross-linking between the two fiber systems imparting subsequent durability (Nawalakhe et al 2015). Pure chitosan microfibers produced by wet spinning process was aimed for possible stable 3-D scaffold woven or nonwoven textile fabrics to be used in regenerative medicine such as bone and cartilage engineering (Toskas et al 2013). Lam et al (2018) examined a blend of chitin fibrils with cotton jersey fabric and showed reduced rigidity that may provide comfort to patients with epidermolysis bullosa skin disease.…”
Section: The Use Of Chitosan In the Textile Sectormentioning
confidence: 99%